2018
DOI: 10.1007/s11033-018-4385-3
|View full text |Cite
|
Sign up to set email alerts
|

Constructing and transient expression of a gene cassette containing edible vaccine elements and shigellosis, anthrax and cholera recombinant antigens in tomato

Abstract: Shigella dysenteriae causing shigellosis is one of the diseases that threaten the health of human society in the developing countries. In Shigella, IpaD gene is one of the key pathogenic genes causing strong mucosal immune system reactions. Anthrax disease is caused by Bacillus anthracis. PA protective antigen is one of the subunits in anthrax toxin complex responsible for the transfer of other subunits into the cytosol of host cells. The 20 kDa subunit of PA (PA20) has the property of immunogenicity. CTxB or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…Studies on vaccine development showed that host cells infected with parasites, viruses, or bacterial pathogens secrete exosomes filled with several antigens of those pathogens [ 128 ]. Experiments in vaccine development showed that cocktail and multi-epitopic vaccines (MEVs) could overcome antigenic escape of pathogens from the immune system [ 129 , 130 ]. Hopefully, using exosome engineering methods, exosomes could be recruited to present multiple antigens as designer vaccine exosomes.…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%
“…Studies on vaccine development showed that host cells infected with parasites, viruses, or bacterial pathogens secrete exosomes filled with several antigens of those pathogens [ 128 ]. Experiments in vaccine development showed that cocktail and multi-epitopic vaccines (MEVs) could overcome antigenic escape of pathogens from the immune system [ 129 , 130 ]. Hopefully, using exosome engineering methods, exosomes could be recruited to present multiple antigens as designer vaccine exosomes.…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%
“…Cholera is a diarrhoeal disease caused by bacteria Vibrio cholerae , a bacterium of comma shape. It colonizes the intestine and produces enterotoxin cholera toxin B (CTB) and causes acute watery diarrhoea [ 78 , 79 ]. When taken orally CTB acts as a mucosal immunogen.…”
Section: Application Of Edible Vaccine In Humans and Animals' Diseasementioning
confidence: 99%
“…Another type of vaccine that is receiving a great deal of attention is subunit vaccines. Today, these vaccines are produced by biotechnology methods, including recombinant DNA technology [12]. These vaccines are produced in various expression systems, such as the E. coli (prokaryotic expression system) or eukaryotic expression systems such as yeast [13], HEK-293 and CHO cell lines [14] as well as plant cells [12].…”
Section: Introductionmentioning
confidence: 99%
“…Today, these vaccines are produced by biotechnology methods, including recombinant DNA technology [12]. These vaccines are produced in various expression systems, such as the E. coli (prokaryotic expression system) or eukaryotic expression systems such as yeast [13], HEK-293 and CHO cell lines [14] as well as plant cells [12]. Due to the antigenic property of HA, NA, and M2e proteins, various studies have been done on the development of a subunit vaccine against influenza virus based on these proteins [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation